1984
DOI: 10.1111/j.1600-0447.1984.tb06859.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Drug Concentrations in Serum and CSF, Clinical Effects and Monoaminergic Variables in Schizophrenic Patients Treated with Sulpiride or Chlorpromazine

Abstract: Schizophrenic patients were treated with fixed doses of sulpiride (800 mg) or chlorpromazine (400 mg) during eight weeks using a double-blind design. In order to examine relationships between pharmacokinetic, clinical and biochemical parameters in relation to treatment the following variables were recorded before and 1, 2, 4 and 8 weeks after treatment. Concentrations of sulpiride, CPZ, 7-OH-CPZ, nor,-CPZ were determined in serum and CSF using liquid chromatography and mass fragmentography. Clinical variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…All patients had measurable amounts of sulpiride or chlorpromazine in serum both in the morning and during the second PET investigation (Table 3). The drug concentrations were in accordance with previous findings (Alfredsson et al 1984). …”
Section: Regions Of Interestsupporting
confidence: 87%
“…All patients had measurable amounts of sulpiride or chlorpromazine in serum both in the morning and during the second PET investigation (Table 3). The drug concentrations were in accordance with previous findings (Alfredsson et al 1984). …”
Section: Regions Of Interestsupporting
confidence: 87%
“…Different antipsychotic drugs and drug metabolites may, however, have different 44 blood-brain distribution ratios because of differences in protein binding in both plasma and CSF (Alfredsson et al 1982(Alfredsson et al , 1984aNyberg et al 1981;Wode-Helgodt & Alfredsson 1981). The dopamine receptor-blocking activity in plasma of psychiatric patients may, therefore, not be directly correlated to neuroleptic-induced dopamine receptor-blocking activity in the brain.…”
Section: Influence Of Blood-brain Distribution On Results Using Radiomentioning
confidence: 91%
“…In a more recent study involving 20 psychotic patients the same group found a significant correlation between reduction in CPRS morbidity scores and chlorpromazine serum concentrations 45 after 1 to 2 weeks, but not after 4 and 8 weeks' treatment with chlorpromazine 400 mg/day (Alfredsson et al 1984a(Alfredsson et al ,b, 1985. The serum chlorpromazine concentrations after 2 weeks' treatment [mean value 88 ± 18 nmol/L (28 ± 6 ILg/L)] were below 200 nmol/L (64 ILg/L) in all but 1 of the 20 patients studied.…”
Section: Concentrations Associated With Therapeutic Responsementioning
confidence: 91%
“…They are understandably 233 counterproductive from a therapeutic point of view. This might explain why some investigators have found an 'inverted U' or 'bell-shaped' concentration-response curve for antipsychotic drugs (Alfredsson et al 1984;Johnstone et al 1983). In addition, it does not seem that using free (i.e.…”
Section: Concentration-effect Relationshipsmentioning
confidence: 95%